2016
DOI: 10.1007/s12035-016-0310-8
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Alpha-7 Nicotinic Acetylcholine Receptor Reduces Brain Edema in Mice with Ischemic Stroke and Bone Fracture

Abstract: Stroke is an important risk factor for bone fracture. We showed previously that bone fracture at the acute stage of ischemic stroke worsens, and activation of α-7 nicotinic acetylcholine receptor (α-7 nAchR) improves, stroke recovery by attenuating inflammation. We hypothesized that activation of α-7 nAchR also improves the blood-brain barrier (BBB) integrity. Permanent distal middle cerebral artery occlusion (pMCAO) was performed on C57BL/6J mice followed by tibia fracture 1 day later. Mice were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“… 14 Following cerebral ischemia, several preclinical studies have observed that both the local upregulation and the pharmacological activation of nicotinic receptors protects the brain against ischemic injury, suggesting the protective central cholinergic effect and the potential role of these receptors as promising inflammatory biomarkers. 15 23 …”
Section: Cholinergic Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 Following cerebral ischemia, several preclinical studies have observed that both the local upregulation and the pharmacological activation of nicotinic receptors protects the brain against ischemic injury, suggesting the protective central cholinergic effect and the potential role of these receptors as promising inflammatory biomarkers. 15 23 …”
Section: Cholinergic Receptorsmentioning
confidence: 99%
“… 22 In contrast, Zou and colleagues examined the effect of α7 nAChRs activation with PHA after cerebral ischemia in mice showing an improvement of the BBB integrity. 16 …”
Section: Cholinergic Receptorsmentioning
confidence: 99%
“…16 We found in our previous studies that tibia fracture occurring either before or after pMCAO exacerbates infarct sizes and sensorimotor dysfunction. [20][21][22][23] However, the impact of BF on post-stroke cognitive function has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological activation of α7 nAChRs with the agonist PHA 568487 has previously shown the reduction of brain edema, ischemic stroke injury, neuroinflammation and oxidative stress following ischemic stroke in mice (Han, Li, et al, ; Han, Shen, et al, ; Zou et al, ). In our study, we explored the effect of PHA on brain edema with T 2 W‐MRI and neuroinflammation by using in vivo [ 18 F]DPA‐714 PET binding following cerebral ischemia (Figure ).…”
Section: Discussionmentioning
confidence: 99%